Endemism and Biogeography of New Zealand Plecoptera (Insecta) - McLellan, Ian (Illiesia, 2006)
New Zealand has 4 families of Plecoptera: Austroperlidae (1 genus); Eusteniidae (1 genus); Gripopterygidae (12 genera); Notonemouridae (7 genera).All genera are endemic except Notonemoura which is shared with Australia. Within New Zealand there are 4 South Island endemic genera; none onNorth Island or Snares; 1 each on Stewart Island, Campbell Island and Auckland Islands. Species endemic to islands are: North and South and Stewart Islands - 5 species from 5 genera; North and South Islands - 16 species from 5genera; North Island - 7 species from 6 genera; South Island - 60 species from 16 genera; all of South Island and Stewart Island - 1 species; Stewart Island - 2 species from 2 genera; Snares - 1 species; Auckland Islands - 4 species from 1 genus; Campbell Island - 2 species from 1 genus. There are no stoneflies on the Chatham and Antipodes Islands. A full list of the 104 described species is given.
Keywords: insekti; Plecoptera; vrbnice; endemiti; Nova Zelandija